Moyamoya syndrome in children with neurofibromatosis type 1: Italian–French experience. Issue 6 (19th April 2017) - Santoro, Claudia; Di Rocco, Federico; Kossorotoff, Manoelle; Zerah, Michel; Boddaert, Nathalie; Calmon, Raphael; Vidaud, Dominique; Cirillo, Mario; Cinalli, Giuseppe; Mirone, Giuseppe; Giugliano, Teresa; Piluso, Giulio; et al.
Abstract : Moyamoya syndrome (MMS) is the most common cerebral vasculopathy among children with neurofibromatosis type 1 (NF1). In this study, we clinically, radiologically, and genetically examined a cohort that was not previously described, comprising European children with NF1 and MMS. The NF1 genotyping had been registered. This study included 18 children. The mean age was 2.93 ± 3.03 years at the NF1 diagnosis and 7.43 ± 4.27 years at the MMS diagnosis. In seven patients, MMS was diagnosed before or at the same time as NF1. Neuroimaging was performed in 10 patients due to clinical symptoms, including headache ( n  = 6), cerebral infarction ( n  = 2), and complex partial seizures ( n  = 2). The remaining eight children (47%) had MMS diagnosed incidentally. Sixteen children were characterized molecularly. The features of MMS were similar between patients with and without NF1. Additionally, the NF1 phenotype and genotype were similar between children with and without MMS. Interestingly, three children experienced tumors with malignant histology or behavior. The presence of two first cousins in our cohort suggested that there may be potential genetic factors, not linked to NF1, with an additional role respect of NF1 might play a role in MMS pathogenesis. The incidental diagnosis of MMS, and the observation that, among children with NF1, those with MMS were clinically indistinguishable from those without MMS, suggested that it might be worthwhile to add an angiographic sequence to brain MRIs requested for children with NF1. A MMS diagnosis may assist in properly addressing an NF1 diagnosis in very young children who do not fulfill diagnostic criteria.